Emisi Metana dan Fermentasi Rumen in Vitro Ransum Hay yang Mengandung Tanin Murni pada Konsentrasi Rendah - A Jayanegara; H. P S Makkar; K Becker (Media Peternakan, 2009)
This experiment was conducted to study the effects of addition of purified tannins at low concentration into hay diet on in vitro gas emission and rumen fermentation. Treatments consisted of: P0 (control hay), P1 (hay + 0.5 mg chestnut tannin/ml of incubation medium), P2 (hay + 0.5 mg/ml mimosa tannin), P3 (hay + 0.5 mg/ml quebracho tannin) and P4 (hay + 0.5 mg/ml sumach tannin). Variables measured were gas production kinetics, organic matter digestibility (OMD), methane production, expressed as percent methane in total gas and methane production per unit organic matter digested, and volatile fatty acid (VFA) production. The results showed that in most cases tannin addition at 0.5 mg/ml decreased significantly (P < 0.05) total and rate of gas production, OMD, total VFA and iso-VFA. Tannin addition also decreased methane production (P < 0.05). Hydrolysable tannins seemed to have better methane reduction effect than condensed tannins. The best tannin to decrease methane was chestnut tannin, which contained hydrolysable tannins. Present research should be shifted from evaluating only the effect of condensed tannins in reducing methane emission towards some potential hydrolysable tannins since the nature and the toxicity of hydrolysable tannins are quite diverse. Key words: methane, tannin, rumen, in vitro, hay